A case report on amphetamine-induced acute pancreatitis with concurrent rhabdomyolysis, acute renal failure and severe hyperkalemia requiring hemodialysis - Nazir, Imran; Abdullah, Hanan M. M.; Sindy, Enas Abdulfattah I.; Boudal, Ehdaa K.; Alwagdani, Abdul Rahman A. Alwagdani; Elsaghir, Ahmed Ramadan M.; H. S. Al Harbi, Samaher; Imran, Haiqa; Elsayed M. Abouelregal, Tareq; Rahman, Sayed S. (International Journal of Research in Medical Sciences, 2026)
Amphetamine toxicity is increasingly linked to complications affecting multiple organ systems, such as rhabdomyolysis, acute kidney injury (AKI), and severe metabolic issues, such as hyperkalemia and high anion gap metabolic acidosis (HAGMA). Although acute pancreatitis due to amphetamines is rare, it should be considered in patients with abdominal symptoms and recent stimulant use. A 33-year-old healthy man presented with a week of epigastric pain, nausea, and vomiting. The patient presented with tachycardia, mild hypotension, and epigastric tenderness. Laboratory tests showed severe hyperkalemia (7.7 mmol/l), metabolic acidosis (pH 7.25, HCO₃⁻ 13.5 mmol/l), elevated creatinine (15.46 mg/dl), lactate (2.6 mmol/l), high CK (25,995 IU/l), and lipase (1,528 U/l). Amphetamines were detected by toxicology screening, and imaging showed interstitial edematous pancreatitis. Initial treatment failed to correct the metabolic issues; however, emergency dialysis led to rapid improvement. He underwent three dialysis sessions, recovered kidney function, and was discharged on day 7 with a follow-up appointment. This case highlights a rare but severe form of amphetamine toxicity, causing acute pancreatitis, rhabdomyolysis, and AKI with life-threatening hyperkalemia. Although amphetamines are not dialyzable, hemodialysis can effectively treat complications such as refractory hyperkalemia and acidosis. Clinicians should be alert to multisystem involvement and recognize that dialysis may be life-saving when standard treatments fail, even if toxin removal is not the main objective of treatment.